Pulmonary Intravascular B-Cell Lymphoma with Angiotropism/Angioinvasion Mimicking Interstitial Lung Disease: A Clinical Dilemma and Potential Diagnostic Challenge. (8th October 2018) - Matea, Florentina; Alowami, Salem; Bonert, Michael; Sur, Monalisa; Shargall, Yaron; Naqvi, Asghar H.
Abstract : Intravascular large B cell lymphoma (IVLBCL) is a rare type of extranodal diffuse large B-cell lymphoma. Patients typically present with nonspecific findings, particularly bizarre neurologic symptoms, fever, and skin lesions. IVLBCL with primary lung presentation is very rare and difficult to diagnose. The authors report a case of a 75-year-old male who presented with neurological symptoms and showed diffuse pulmonary ground glass opacities on computed tomography scan (CT scan). Surgical lung biopsy was performed. Light microscopic examination of the specimen showed diffuse alveolar septal widening caused by neoplastic lymphocytes, which were positive for CD20. These atypical lymphoid cells also demonstrated angiotropism/angioinvasion of the medium sized pulmonary vessels. The patient was diagnosed with IVLBCL and underwent chemotherapy. The patient is still alive 12 months after diagnosis.